A check-list of the Odonata from the eastern region of Bangladesh With sometaxonomic notes (University Journal of Zoology, Rajshahi University, 2012)
A survey of the Odonate fauna was conducted in the Sylhet and Srimangal Districts of Sylhet Division and Chittagong, Khagrachari, Rangamati, Bandarban and Coxs Bazar Districts of Chittagong Division. The designated areas were visited periodically for nearly seven years from 1994 to 2000. The present paper includes a list of the odonate species collected during the survey period. A total of 764 specimens were collected which comprised 49 species of Anisoptera in 32 genera, and 47 species of Zygoptera in 18 genera. Of these 15 species in 8 genera of the former and 27 species in 11 genera in the latter suborder are new records from Bangladesh. The collection also includes females of three species and males of two species that happen to be new to science. The specimens are preserved in our personal collection.DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10755Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 61-66